2020
DOI: 10.1055/a-1236-4542
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging features of the normal parathyroid gland in the dog

Abstract: Zusammenfassung Gegenstand und Ziel Ziel dieser prospektiven Pilotstudie war zu beurteilen, ob die physiologische Glandula parathyroidea beim Hund computertomografisch dargestellt werden kann, und eine Beschreibung ihres CT-Erscheinungsbildes zu geben. Material und Methoden In die Studie wurden 25 Hunde aufgenommen, bei denen aufgrund von Erkrankungen im Halsbereich ohne Bezug zu Schild- oder Nebenschilddrüse ein CT-Scan erfolgte. Einschlusskriterium waren unauffällige Befunde bei der allge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
(34 reference statements)
6
6
0
Order By: Relevance
“…The size of the normal parathyroid glands in CT was recently described to be 4.2 × 2.5 × 2.9 mm (length, width and height) [13]. In the majority of the cases included in the current study, the measured size of the abnormal parathyroid glands was larger than the reported range, as previously reported for US [6,10,15].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The size of the normal parathyroid glands in CT was recently described to be 4.2 × 2.5 × 2.9 mm (length, width and height) [13]. In the majority of the cases included in the current study, the measured size of the abnormal parathyroid glands was larger than the reported range, as previously reported for US [6,10,15].…”
Section: Discussionsupporting
confidence: 62%
“…All the parathyroid glands included in this study showed hypoattenuating parenchyma (both pre-and post-contrast administration) with respect to the adjacent thyroid gland. This is reported to also be the CT appearance of the normal parathyroid glands in dogs [13]. Similarly, the US echogenicity of abnormal parathyroid glands was reported to be hypo to anechoic, as for the normal parathyroid glands, therefore making the echogenicity not useful to diagnose parathyroid gland disease [10].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Contrast-enhanced scans did not show more glands compared to plain CT. The authors of that study suggest, that the reported glands’ dimensions should be treated with caution due to the difficulties in precisely defining their margins [ 28 ]. In the current study, similarly, the parathyroid glands were not always visible and their ill-defined margins limited precise measurements.…”
Section: Discussionmentioning
confidence: 99%